Human rights-based approach to global surgery: A scoping review. (October 2020) - Ma, Xiya; Marinos, John; De Jesus, Jana; Lin, Nicole; Sung, Chia-Yen; Vervoort, Dominique
Abstract: Background: Health is a basic human right, yet surgery remains a neglected stepchild of global health. Worldwide, five billion people lack access to safe, timely, and affordable surgical and anesthesia care when needed. This disparity results in over 18 million preventable deaths each year and is responsible for one-third of the global burden of disease. Here, we evaluate the role of surgical care in protecting human rights and attempt to make a human rights argument for universal access to safe surgical care. Material and methods: A scoping review was done using the PubMed/MEDLINE, Embase, and Scopus databases to identify articles evaluating human rights and disparities in accessing surgical care globally. A conceptual framework is proposed to implement global surgical interventions with a human rights-based approach. Results: Disparities in accessing surgical care remain prevalent around the world, including but not limited to gender inequality, socioeconomic differentiation, sexual stigmatization, racial and religious disparities, and cultural beliefs. Lack of access to surgery impedes lives in full health and economic prosperity, and thus violates human rights. Our normative framework proposes human rights principles to make surgical policy interventions more inclusive and effective. Conclusion: Acknowledging human rights in the provision of surgical care around the world is critical to attain and sustain the Sustainable Development Goals and universal health coverage. National Surgical, Obstetric, and Anesthesia Planning and wider health systems strengthening require the integration of human rights principles in developing and implementing policy interventions to ensure equal and universal access to comprehensive health care services. Highlights: 18 million people die every year due to lack of access to surgical care. Surgery, obstetrics, and anesthesia are neglected within the human rights discourse. A conceptual framework is developed to integrate human rights within global surgery. Recognition of surgical care as a right is essential to improve access to surgical care.